Nurse-physician communication - An integrated review - Tan, T.; Zhou, Huaqiong; Kelly, Michelle (Wiley-Blackwell Publishing, 2017)
Aim and objective: To present a comprehensive review of current evidence on the factors which impact on nurse-physician communication and interventions developed to improve nurse-physician communication. Background: The challenges in nurse-physician communication persist since the term 'nurse-doctor game' was first used in 1967, leading to poor patient outcomes such as treatment delays and potential patient harm. Inconsistent evidence was found on the factors and interventions which foster or impair effective nurse-physician communication. Design: An integrative review was conducted following a five-stage process: problem identification, literature search, data evaluation, data analysis and presentation. Methods: Five electronic databases were searched from 2005 to April 2016 using key search terms: "improve*," "nurse-physician," "nurse," "physician" and "communication" in five electronic databases including the Cumulative Index to Nursing and Allied Health Literature (CINAHL), MEDLINE, PubMed, Science Direct and Scopus. Results: A total of 22 studies were included in the review. Four themes emerged from the data synthesis, namely communication styles; factors that facilitate nurse-physician communication; barriers to effective nurse-physician communication; and interventions to improve nurse-physician communication. Conclusion: This integrative review suggests that nurse-physician communication still remains ineffective. Current interventions only address information needs of nurses and physicians in limited situations and specific settings but cannot adequately address the interprofessional communication skills that are lacking in practice. The disparate views of nurses and physicians on communication due to differing training backgrounds confound the effectiveness of current interventions or strategies. Relevance to clinical practice: Cross-training and interprofessional educational from undergraduate to postgraduate programmes will better align the training of nurses and physicians to communicate effectively. Further research is needed to determine the feasibility and generalisability of interventions, such as localising physicians and using communication tools, to improve nurse-physician communication. Organisational and cultural changes are needed to overcome ingrained practices impeding nurse-physician communication.